Amelogenesis Imperfecta and Generalized Gingival Overgrowth Resembling Hereditary Gingival Fibromatosis in Siblings: A Case Report. (9th October 2012) - Yaprak, Emre; Subaşı, Meryem Gülce; Avunduk, Mustafa; Aykent, Filiz
Abstract : Amelogenesis imperfecta (AI) is a group of hereditary disorders primarily characterized by developmental abnormalities in the quantity and/or quality of enamel. There are some reports suggesting an association between AI and generalized gingival enlargement. This paper describes the clinical findings and oral management of two siblings presenting both AI and hereditary gingival fibromatosis (HGF) like generalized gingival enlargements. The treatment of gingival enlargements by periodontal flap surgery was successful in the management of the physiologic gingival form for both patients in the 3-year follow-up period. Prosthetic treatment was also satisfactory for the older patient both aesthetically and functionally.